VIABILITY OF LACTIC CULTURES BEFORE AND AFTER FREEZE DRYING IN POMEGRANATE JUICE - RITA NARAYANAN (The Bioscan, 2019)
The purpose of this research was to study the viability of lactic cultures in pomegranate juice before and after freeze drying.Two dietary adjuncts of a combination of 50% pomegranate juice and 50% skim milk were fermented separately with 1% culture of Lactobacillus plantarum and Lactobacillus casei and freeze-dried. The viability of the freeze-dried strains was evaluated after 24 h on MRS agar. Results indicated a 2 log reduction in the viability of lactic cultures in fermented combination of pomegranate juice and skim milk and also in fermented skim milk (control) after freeze-drying . The viable count of L.casei after freeze drying was reported as 8.04±0.1470log 10 cfu/ml and 8.030± 0.1483log 10 cfu/ml in control and pomegrante juice and skim milk mixed sample respectively . The viable count of L. plantarum after freeze drying was reported as 8.04±0.1470log 10 cfu/ ml and 8.02±0.0151log 10 cfu/ml in control and pomegrante juice and skim milk mixed sample respectively . Survival of the lactic cultures were studied after freeze drying at intervals of 7 days, 15 days, 30 days and 90 days of storage under refrigeration conditions. A higher percent of survival was noted upto 30 days in both the lactic organisms in skim milk (control) and fermented combination of pomegranate juice with skim milk . However there was a reduction in viability of both the cultures on the 90th day of enumeration.